Public spending and its impact on the pre-WWII Greek economy: A comparative analysis for civilian and military expenditure - Chrestos Kollias; Michael S. Zumpulakes; Suzanna-Maria Paleologou; Panayiotis Tzeremes (The Journal of European Economic History (JEEH), 2021)
This paper examines the economic effects of public spending onGreek economic growth over the period 1842-1938. In less devel-oped countries, such as late-19th- and early-20th-century Greece, pub-lic spending played an important role in the construction of keyinfrastructures and the provision of basic public health and educationsystems. Such expenditures augment physical and human capital,enhancing aggregate production possibilities and boosting growthand development. As has been shown, the composition of publicspending can be an important determinant of its impact on a coun-try's level of economic development. To test for such differential com-position effects, the Greek public spending time series was dividedinto two broad categories: civilian and military expenditure. The resultsreported here point to a significant positive effect on growth in thecase of civilian expenditure but not for military spending.
Keywords: 330